The impact of soft-skills training for entrepreneurs in Jamaica - Diego Ubfal; Irani Arraiz; Diether W. Beuermann; Michael Frese; Alessandro Maffioli; Daniel Verch (Inter-American Development Bank (IDB), 2020)
A randomized controlled trial with 945 entrepreneurs in Jamaica shows positive short-term impacts of soft-skills training on business outcomes. The effects are concentrated among men and disappear 12 months after the training. The main channel is increased adoption of recommended business practices, exclusively observed in the short run. Persistent effects were observed on an incentivized behavioral measure of perseverance after setbacks, a focus of this training. An intensive course on soft-skills was compared to one that combines soft-skills with traditional business training. The effects of the combined training are never statistically significant.
Keywords: J24; L25; M13; O12; 330; business training; entrepreneurship; soft skills